2016
DOI: 10.5194/isprs-annals-iii-2-91-2016
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATING THE EFFECTS OF REDUCTIONS IN LiDAR DATA ON THE VISUAL AND STATISTICAL CHARACTERISTICS OF THE CREATED DIGITAL ELEVATION MODELS

Abstract: With continuous developments in LiDAR technologies high point cloud densities have been attainable but accompanied by challenges for processing big volumes of data. Reductions in high point cloud densities are expected to lower data acquisition and data processing costs; however this could affect the characteristics of the generated Digital Elevation Models (DEMs). This research aimed to evaluate the effects of reductions in airborne LiDAR point cloud data densities on the visual and statistical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
4
1
Order By: Relevance
“…The MAD and SD for the UAV point cloud (0.11 m and 0.39 m, respectively) were significantly higher than for the LiDAR data (0.002 m and 0.03 m, respectively). Those results are in line with the findings presented in the work of [19] and with results obtained comparing both point clouds using the DoD method (previous section).…”
Section: Suitability Of the Proposed Methods To Produce Dem From Uav Asupporting
confidence: 92%
See 1 more Smart Citation
“…The MAD and SD for the UAV point cloud (0.11 m and 0.39 m, respectively) were significantly higher than for the LiDAR data (0.002 m and 0.03 m, respectively). Those results are in line with the findings presented in the work of [19] and with results obtained comparing both point clouds using the DoD method (previous section).…”
Section: Suitability Of the Proposed Methods To Produce Dem From Uav Asupporting
confidence: 92%
“…Reduction of point cloud density decreases the data acquisition and data processing costs, but can affect the accuracy of the generated model. Alas, the author of [19] reported a 50% reduction of LiDAR point density without big deteriorations in the visual and statistical characteristics of the generated DEMs. The results in [20] showed that data with 50% reduction provided compatible surface estimation, but significantly reduced half of the processing time and storage space.…”
Section: Dem Generation From Point Cloudsmentioning
confidence: 99%
“…All these increases are lower than those reported by Anderson et al [18] and Liu et al [19]. Nevertheless, Asal [2] reported an increase of RMSE of approximately 260% when the point cloud was reduced to 6%. For each density value studied, the RMSE values derived from the four interpolators were ordered from lowest to highest as follows: IDW, KR, TLI, and the worst values were found for RBF.…”
Section: Discussionmentioning
confidence: 55%
“…It is usually used for describing terrains, giving its elevations without considering the vegetation or man-made features. It plays an important role in applications related to terrain modeling, hydrological modeling, or landscape evolution due erosion process [1][2][3]. When a high scale is required, it is very important to count with a point cloud which yields a high resolution and high quality DEM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation